ON THE SYNONYMY BETWEEN SPINITECTUS INDICUS VERMA AND AGARWAL, (1932) AND S. MUELLERI GUPTA AND VERMA (1927) - SAHLAY, PUNAM; SAHLAY, UMAPATI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
Spinitectus indicus Verma and Agarwal (1932), a nematode belonging to the genus Spinitectus Fourment, 1946 (Spinitectinae S. kirjabin, 1946) is parasitic in fish hosts like Pseudotropius garua, Eutropiichty's vacha, Wallago attu and Notopterus notopterus and is distributed to Allahabad, Lucknow (U.P.) and Dacca (Bangladesh). In the year 1977 Gupta & Verma reported another species S. muelleri from Notopterus notopterus at Lucknow. The latter species was given an independent status by Gupta & Verma (1977). Soota (1983) though said that the above two nematodes are synonyms but failed to give any plausible reason in such a synonymy. The present authors have consulted the original papers of Verma & Agarwal (1932) and Gupta & Verma (1977), and have compared the different parameters of two nematodes under study. The authors have definite reason, in considering S. muelleri Gupta & Verma (1977), a synonym of S. indicus Verma & Agarwal (1977).